2019
DOI: 10.1007/s00404-019-05278-7
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative hypoalbuminemia is associated with complication rate and overall survival in patients with vulvar cancer undergoing surgery

Abstract: ObjectiveHypoalbuminemia, a known marker for malnutrition, has been associated with an increased risk for perioperative morbidity and poor prognosis in patients with solid tumors. The aim of this study was to investigate the prognostic and predictive value of pre-treatment serum albumin levels for survival and postoperative complications in patients with vulvar cancer undergoing surgery.MethodsWithin in this retrospective study, we assessed data of 103 consecutive patients with vulvar cancer undergoing primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Another study investigated the prognostic role of serum ALB in patients with advanced HNSCC who underwent surgery and flap reconstruction and determined that preoperative hypoalbuminemia was a poor prognostic indicator in this population [29]. Also, studies have shown that low serum ALB is an unfavorable determinant in other malignancies, including oral, breast, and vulvar cancers [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Another study investigated the prognostic role of serum ALB in patients with advanced HNSCC who underwent surgery and flap reconstruction and determined that preoperative hypoalbuminemia was a poor prognostic indicator in this population [29]. Also, studies have shown that low serum ALB is an unfavorable determinant in other malignancies, including oral, breast, and vulvar cancers [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Preexisting hypoalbuminemia is a prognostic indicator of worse outcome for a broad spectrum of diseases ranging from medical conditions [ 64 , 65 , 66 ] to surgery [ 67 ]. Evidence in support of a prognostic role of serum albumin level is abundant and established for orthopedic [ 68 , 69 , 70 , 71 ], cardiovascular [ 72 , 73 ], gynecologic [ 74 , 75 ], and visceral surgery [ 76 , 77 , 78 ].…”
Section: Hypoalbuminemia and Disease Outcomesmentioning
confidence: 99%
“…Among these patients, the rates of postoperative complications were higher when compared to patients with a normal nutritional status. Moreover, the authors underlined the fact that lower preoperative serum albumin levels were associated with significantly poorer rates of overall survival in both univariate and multivariate analyses, and thus, demonstrating the importance of this parameter (18). In another study that also investigated the influence of the preoperative serum levels of albumin on the postoperative outcomes, the authors demonstrated that hypoalbuminemia is significantly associated with the risk of wound complication even after adjusting for age, body mass index, preoperative hematocrit or association of diabetes (19).…”
Section: Discussionmentioning
confidence: 94%
“…More specifically, a lower level of preoperative albumin caused by malnutrition and albumin synthesis suppression as a consequence of a systemic inflammatory response is responsible for a higher rate of postoperative morbidity (14)(15)(16)(17). In a recent study conducted by Bekos et al in 2019, the authors included 103 patients submitted to vulvar cancer surgery, nine of whom presented with preoperative hypoalbuminemia (18). Among these patients, the rates of postoperative complications were higher when compared to patients with a normal nutritional status.…”
Section: Discussionmentioning
confidence: 99%